إدراك المستهلك الجزائري لمزايا وخصائص التسويق عبر الهواتف الذكية -دراسة ميدانية على عينة من المستهلكين المستخدمين لأجهزة الهواتف الذكية لمؤسسة كوندور بولاية غرداية- - معراج, هواري; ثامر, محمد البشير (جامعة الوادي - University of Eloued, 2017)
Algerian custumer perception for marketing characteristics and adventagesthroughout smartphones, a fieldstudy on usersspecimen of smartphones for condor’scompany in the southern province Ghardaia, The purpose behind the study is to know to what extent the algerian customers perceive the adventages and charcteristics which marketing provids throughout smartphones. that’s by an inquiry about customers specimen of Condor smartphones Algerian company in the southern province Ghardaia. The study society was chosen among the algerian customers ,where the inquiry has taken a specimen of eighty customers using condor smartphones algerian company from the southern province Ghardaia, The study realized that it exists an important impact for marketing characteristics and adventages by smartphones especialy : Privacy respect, easiness in use, fast application and free choice on perception operation , then encouraging the Algeian customer on marketing across smartphones throughout the application being provided by Condor Algerian company, Never the less, the big restraint and challenge wich faces the algerian customer in marketing by smartphones, is the improvided electronic payement mechanism, adding to that lawlessness in protecting and preventing customers across smartphones. The study urges to find practical solutions, that is by reforming the algerian monitory system wichc ontributes to solve electronic payment problematic in a hand, and spread a positive impact on motivat in electronic buying behaviour by smart phones on the other hand. That need salso to adapt the legislative system and restore it according to the contemporary needs and developing technologies, media and communications
مقال
Keywords: التسويق عبر الهواتف الذكية ، الخصوصية ، الدفع الالكتروني، إدراك المستهلك; marketing across smartphones. Privacy. Electronicpayment. Customer perception